2014
DOI: 10.1080/00103624.2013.872250
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Nutrient Balance, Soil Quality, and Sustainability of Rice (Oryza sativaL.) under Organic and Conventional Production Systems

Abstract: covering 10 crop seasons [five wet (WS; Kharif) and five dry (DS; Rabi)] at the Directorate of Rice Research farm, Hyderabad, India, to compare the influence of organic and conventional farming systems on productivity of fine grain rice varieties, cumulative partial nutrient balance, and soil health/quality in terms of nutrient availability, physical and biological properties, and sustainability index. Two main plot treatments were with and without plant protection measures, and four subplot treatments were (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A set of 300 RILs (F 8 ) were grown in two replications in an augmented block design at the research farm of ICAR-Indian Institute of Rice Research (IIRR), Hyderabad during wet season 2011 following recommended package of practices. The experimental soil characteristics were: pH 8.2; non-saline (EC 0.7l dS/m); calcareous (free CaCO 3 5.01%); CEC 44.1 C mol (p+)/kg soil and medium soil organic carbon (0.69%); low soil available nitrogen (228 kg ha -1 ); high available phosphorus (105 kg P 2 O 5 ha -1 ), high available potassium (530 kg K 2 O ha -1 ), and high available zinc (12.5 ppm) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…A set of 300 RILs (F 8 ) were grown in two replications in an augmented block design at the research farm of ICAR-Indian Institute of Rice Research (IIRR), Hyderabad during wet season 2011 following recommended package of practices. The experimental soil characteristics were: pH 8.2; non-saline (EC 0.7l dS/m); calcareous (free CaCO 3 5.01%); CEC 44.1 C mol (p+)/kg soil and medium soil organic carbon (0.69%); low soil available nitrogen (228 kg ha -1 ); high available phosphorus (105 kg P 2 O 5 ha -1 ), high available potassium (530 kg K 2 O ha -1 ), and high available zinc (12.5 ppm) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…This indicates a positive residual effect on nutrient availability with OF. Surekha and Satishkumar (2014) also reported that organic farming needed more than two years to stabilize rice productivity and bring about perceptible improvement in soil quality and sustainability in irrigated rice. The mean straw yield of rice under OF (5720 kg ha −1 ) was comparable to that under CF (5930 kg ha −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The soil under ZT found containing less available K than CT at Regional Agricultural Research Station, Tarahara (Sinha et al 2019). Furthermore, negative K balance for crops in South Asia is widespread (Singh et al 2005, Surekha andSatishkumar 2014).…”
Section: Discussionmentioning
confidence: 99%